Biportal endoscopic bilateral decompression in lumbar spinal stenosis: a 3-year retrospective cohort study - Li, Dongyue; Cheng, Yunzhong; Yin, Peng; Su, Qingjun (Frontiers in Surgery, 2025)
BackgroundBiportal endoscopic bilateral decompression (BEBD) has gained recognition for treating lumbar spinal stenosis (LSS) through preservation of posterior spinal structures while achieving bilateral neural decompression. However, the relationship between postoperative radiographic findings and clinical outcomes remains unclear. This study investigates clinical efficacy, radiographic findings, and their potential correlations following BEBD.MethodsA retrospective cohort analysis of 51 LSS patients undergoing BEBD (January 2020–December 2021) was conducted. Intraoperative parameters, complications, and clinical outcomes [Visual Analog Scale (VAS), Oswestry Disability Index (ODI), Modified Macnab criteria] were evaluated preoperatively, at 1 month, and final follow-up. Radiographic parameters included medial facetectomy surface angle (MFSA), facet joint preservation rate (FJPR), lateral recess decompression rate (LRDR), dural sac cross-sectional area expansion rate (DSCAER), and segmental range of motion (SROM).ResultsThe procedure demonstrated the mean operative time of 93.6 ± 13.7 min, with follow-up 36–60 months (mean 42.5 ± 6.7 months). Clinically, lower back pain (VAS: 5.9 ± 0.9–2.3 ± 0.6 at 1 month; 0.6 ± 0.5 final) and leg pain (6.8 ± 0.9–1.7 ± 0.6 at 1 month; 0.5 ± 0.6 final) showed sustained, statistically significant reductions (P < 0.05). Functional recovery was marked by ODI improvements from 64.5 ± 7.5 preoperatively to 26.1 ± 2.8 (1 month) and 11.0 ± 2.3 (final) (P < 0.05), with 88.24% (45/51) achieving excellent/good outcomes by modified Macnab criteria. Radiographically, MFSA remained <90°, FJPR exceeded 70%, and DSCAER expanded by 95.19 ± 22.5% (P < 0.05), while SROM stability was preserved (P > 0.05). Notably, no radiographic findings correlated with clinical outcomes stratification (P > 0.05), underscoring the multifactorial nature of postoperative success.ConclusionsBEBD demonstrates significant clinical improvement in LSS patients, with marked DSCA expansion and preserved FJ stability. The technique achieves effective bilateral decompression with preserved biomechanical stability. Radiographic findings showed no correlation with clinical success, indicating multifactorial postoperative influences.